Identificación de los elementos culturales de la comunidad Quilajaló para el fomento del desarrollo turístico sostenible de la parroquia San Miguel del cantón Salcedo de la provincia de Cotopaxi. - Abad Sarango, Mónica Elizabeth (2021)
Tourism represents a sustainable economic activity, since it is the natural and cultural resources of the destination territories that manage to generate an alternative development. The cultural references of the Quilajaló community are present, they are part of the cultural, historical and landscape accumulation without having been used for tourist dissemination and are part of the additional economic alternatives of the community. As a priority, productive promotion and economic improvement, sustainable tourism poses the identification of Quilajalo's tourism references, through participatory prioritization and through the collection of primary information. There is testimonial and bibliographic information, and from this design a proposal for the generation of at least two communication products that will be used as instruments of mass promotion, finally the communication products are validated with the community. For the development of this project, a mixed methodology is used, as it focuses on the qualitative paradigm, being a subject with a social tint and in context with reality, and also makes use of a quantitative paradigm, since the project generates data that must be recorded and interpreted. The identification of the main cultural elements in Quilajaló allowed to establish a first advance in the tourism promotion of the community, this as a resource to open the promotion of sustainable tourism development.